Approaching the Century Jubilee (Interview with the Rector D.A. Endovitsky) - D. A. Endovitsky (Высшее образование в России)
In his interview, the Rector of Voronezh State University highlights the milestones of VSU’s history and its achievements during the centennial  working experience. The history of Voronezh State University goes back to  1918, when the staff and students of Yuriev (former Derpt) University moved to Voronezh owing to the German occupation of Estonia. Today Voronezh  State University is one of most renowned universities in Russia, the largest  research university in the Central Black Earth Region. Its world  competitiveness can be demonstrated by the fact that VSU is listed among  the top universities in international and national rankings such as  Quacquarelli Symonds (QS) World University Ranking, Times Higher  Education (THE) World University Ranking, Interfax, Rating of Russian  universities. The advanced forms of interaction between University and  business partners and enterprises were described, such as centers of  corporate training (VSU has more than 10) and corporate postgraduate  courses (cooperation with PriceWaterhouseCoopers, Bionorica SE and  others). The University is piloting the convergent educational programs, e.g. “Medical cybernetics”, mathematical modeling in pharmaceutical studies,  experimental technical school for gifted children.